Serum variations of anti-mullerian hormone and total testosterone with aging in healthy adult Iranian men: A population-based study - Ramezani Tehrani, Fahimeh; Mansournia, Mohammad Ali; Solaymani-Dodaran, Masoud; Minooee, Sonia; Azizi, Fereidoun (PLOS ONE, 2017)
Background Literature proves anti-mullerian hormone (AMH) and total testosterone (TT) as two important reproductive hormones in male development, however evidence regarding age variations of these hormones is lacking. Aims To estimate the normal serum AMH values and to assess the age-specific TT levels in men aged 30–70, we conducted the present population-based study. Methods A total of 831 healthy eligible men, aged 30–70 years, were recruited from Tehran Lipid and Glucose study cohort. Centiles for AMH were estimated according to the exponential normal 3-parameter model. The parametric method of Royston available in general software was applied for the first time to estimate the age-specific AMH and TT percentiles of 5th, 10th, 25th, 50th, 75th, 90th and 95th. Results Mean AMH level was 6.93, ranging from 0.1 to 40.1 ng/ml. Serum AMH concentrations followed a steady reduction with increasing age. Mean TT level was 4.8, ranging from 0.44 to 11.4 ng/ml. Discussion A measurable serum concentrations of AMH in healthy males throughout lifespan with variations, based on age, confirming a slight age-related AMH decline. Fractional polynomial (FP) regression models revealed that the mean and standard deviation (SD) of the TT were not associated with age, so the percentiles estimated were not age-specific. Conclusion We presented a nomogram of age-specific AMH values in a healthy cohort of Iranian men. This finding might have clinical importance in dealing hormonal disorders in men.